Experimental investigation of green brick shrinkage behavior with Bigot's curves - MANÇUHAN, EBRU; SAYAN, PERVİZ; SARGUT, SİBEL (TAYLOR & FRANCIS INC, 2016)
The objective of this work is to define the convenient drying parameters such that the energy consumption in the brick drying process is minimized. This is an experimental study where the challenge lies in the mechanical resistance of the dried bricks which must satisfy the quality standards despite the reduction of energy consumption and the drying time. Firstly, we run multiple drying process tests and gather experimental data, and then discover the most suitable drying conditions. Secondly, the overall drying rate is improved using a Bigot's curve analysis on the most suitable drying conditions. The results show that the drying rate increases significantly in conjunction with shorter drying time and lower energy consumption.
Keywords: Bigot curves; critical moisture; drying shrinkage; green brick; DRYING CONDITIONS; POROUS MATERIALS; MASS-TRANSFER; CLAY; SIMULATION; CERAMICS; SPAIN